Microfacies and Paleoenvironment Conditions of Kometan Formation in Dokan area, northeast of Iraq - Mustafa, Ibraheem (ASJ - Academic Science Journal, 2025)
The well-bedded and white chalky to white grey limestone of the Kometan Formation is Late Turonian – Santonin in age. The rock samples were taken from Qalat area in the Sulaymaniyah governorate in northern Iraq and studied under many different microscopes.The main aims of the paper are to study the microfacies of the Kometan Formation and interpretation of the paleodepositional environment based on the detailed examination of thin sections prepared from samples selected from the Kometan Formation.Muddy, marly, and brecciated limestone are the lithology of the Kometan Formation determined by petrographic studies based on the characteristics of grain and matrix types. The microfacies analysis of the samples from the Kometan Formation revealed three main microfacies and two submicrofacies. The first one is foraminiferal lime mudstone, these microfacies existed in the first part of the formation after the Shiranish Formation characterized by a significant amount of micrite with few amount of fossil content. The second one is wackestone microfacies, with two submicrofacies including Oligosteginal wackestone submicrofacies and Globotruncana wackestone submicrofacies. These microfacies are characterized by a considerable number of skeletal grains and the groundmass consists of micritic materials. The microfacies are located in the center of the formation and contain the major stylolite with a high ratio of chert nodules. The third main microfacies is planktonic foraminiferal packstone microfacies, these microfacies are characterized by a high ratio of skeletal grain and a minor amount of micrite which form the groundmass of the facies. This microfacies is exposed at the adjacent zone to the major fault between Kometan and Qamchuqa formations. The paleoenvironment of the Kometan Formation is a deep-shelf marine environment passed to the continental slope environment based on the grain type characteristics and depositional textures identified in the present study.